Artemisia verlotiorum (Asteraceae) in the continental part of Ukraine: now in Kyiv - Mosyakin, S.L.; Boiko, G.V.; Glukhova, S.A. (Український ботанічний журнал, 2019)
Colonies of Artemisia verlotiorum (Asteraceae), an alien species of East Asian origin now widespread in many countries of the world, were found in 2018 in Kyiv in the Syrets Arboretum (Syretskiy Dendropark) and in a nearby abandoned plant nursery and greenhouses. At present, three clonal colonies have been revealed. Most probably rhizomes of that species were initially introduced to Kyiv with soil and/or imported trees and/or shrubs. However, one colony (along the wall of the administrative building of the arboretum) most probably emerged from seeds dispersed by wind from the main (supposedly initial) colony in the abandoned nursery. Before our find in Kyiv, A. verlotiorum was reliably known in Ukraine in Crimea (reported since the 1920s), Transcarpathia, and from Lviv (recent records, to be discussed in detail in a forthcoming article). Most probably A. verlotiorum is spreading in Eastern Europe mainly by rhizome fragments with soil and plant material. Other alien taxa of the Artemisia vulgaris group (especially A. umbrosa and A. argyi) occur in Ukraine mainly as "railroad" plants.